The Influence of Social Media Activities, Brand Equity, E-WOM, on Instagram on Customer Purchase Interest in Purchasing Skincare Products - Ali Imron (Yayasan Gema Bina Nusantara, 2023)
This research aims to analyze whether there is an influence of social media activities, brand equity, and e-WOM on buying interest. This research uses quantitative research methods. The population chosen for this research were teenagers and adults who were at least 17 years old and knew or had ever used skincare products. This research uses a survey research method, such as filling out a questionnaire. The research results show that the content on Instagram for skincare products is also considered interesting by respondents and can make it easier for consumers to express their opinions. With Instagram, consumer attention on social media is also influenced positively. The majority of respondents also have the potential to repurchase skincare products and are willing to recommend them to others. Content on Instagram for skincare products can have a buying effect on respondents and make them customers. Respondents also buy products offered on Instagram more often.